Axial behaviour of square stub CFST columns strengthened with square steel tube and HPC jacket. (November 2021) - Huang, Yue; Liang, Hongjun; Lu, Yiyan; Zhu, Tao
Abstract: This study examines the performance of 26 concrete-filled steel tube square stub columns strengthened with square steel tube and concrete jacket, 21 steel tubes were infilled with high-performance concrete (HPC) jackets and 5 were infilled with ordinary concrete (OC). The test results of the failure modes, load–axial shortening curves, ductility index, and strain analysis revealed that no evident effect was observed on the load-bearing capacity when steel fibre-reinforced concrete (SFC) or self-stressing concrete (SSC) alone was used; however, an enhancement was achieved with the combination, i.e., steel fibre-reinforced self-stressing concrete (SFSSC). The results also indicated that SFC demonstrated a positive effect on ductility, whereas SSC decreased the deformation capacity. A finite element model was established for further analysis of retrofitted columns and comparison of the failure modes and load-shortening curves with the experimental results. The model was used to analyse the confinement of the concrete jacket and inner concrete. The curves of the load on the components indicated that the contribution of the concrete jacket to the peak load was lower than that of the outer tube owing to the uneven confinement effect, and the different types of concrete jackets only affected the load they bore. Based on the numerical database, equations for predicting the ultimate strengths of retrofitted columns with OC were proposed. A coefficient related to SSC was considered in the equations for predicting the capacities of columns with HPC. The calculated results showed good agreement between the experimental and numerical results. Graphical abstract: Unlabelled Image Highlights: Axial behavior of square stub CFST columns strengthened with steel tube and HPC jacket was studied. The combination of steel fibers and self-stressing improved the load-bearing capacity while maintaining good ductility. Confinement effect on the concrete and load on components were studied using a verified FE model. Equations for predicting the self-stressing and capacities were proposed.